Community circles: Mitigating the impact of trauma on the middle school student. Issue 4 (8th August 2019) - Silverman, Jamie; Mee, Molly
Abstract: This article posits that the restorative practice of community circles offers middle school students a safe, empowering space where moments of social and emotional strife can be addressed and possibly prevented. It also recognizes that by creating a safe and empowering classroom community, students who have or are experiencing trauma can find comfort in knowing that a safe space where their voices can be heard is available to them.